Characterization of corrosion scale formed on stainless steel delivery pipe for reclaimed water treatment. (1st January 2016) - Cui, Yong; Liu, Shuming; Smith, Kate; Yu, Kanghua; Hu, Hongying; Jiang, Wei; Li, Yuhong
Abstract: To reveal corrosion behavior of stainless steel delivery pipe used in reclaimed water treatment, this research focused on the morphological, mineralogical and chemical characteristics of stainless steel corrosion scale and corroded passive film. Corrosion scale and coupon samples were taken from a type 304 pipe delivering reclaimed water to a clear well in service for more than 12 years. Stainless steel corrosion scales and four representative pipe coupons were investigated using mineralogy and material science research methods. The results showed corrosion scale was predominantly composed of goethite, lepidocrocite, hematite, magnetite, ferrous oxide, siderite, chrome green and chromite, the same as that of corroded pipe coupons. Hence, corrosion scale can be identified as podiform chromite deposit. The loss of chromium in passive film is a critical phenomenon when stainless steel passive film is damaged by localized corrosion. This may provide key insights toward improving a better comprehension of the formation of stainless steel corrosion scale and the process of localized corrosion. The localized corrosion behavior of stainless steel is directly connected with reclaimed water quality parameters such as residual chlorine, DO, Cl − and SO4 2− . In particular, when a certain amount of residual chlorine in reclaimed water is present as an oxidant, ferric iron is the main chemical state of iron minerals. Graphical abstract: Highlights: Stainless steel corrosion scale is identified as podiform chromite deposit. The loss of chromium in passive film is a critical phenomenon of localized corrosion. Stainless steel localized corrosion is connected with reclaimed water quality. Crevice corrosion with pit corrosion is the dominant form for stainless steel.